Os limites cognitivos no incidente de desconsideração da personalidade jurídica em execução de título executivo extrajudicial - Gomes, Roberta Freitas (2024)
The present study is dedicated to analyzing the limits of cognition in the incident of disregard of legal personality, seeking to answer, specifically, the following question: cognition in the incident of disregard of legal personality is limited, and must adhere to the assumptions of disregard of legal personality, or could it cover the merit of the obligation, the debt itself? The aim is to demonstrate, in the end, that cognition in the incident is limited due to the object of litigation and that, as he is not a party to the execution, the defendant in the incident cannot discuss the debt in his defense. Throughout the study, a qualitative approach methodology was adopted, using bibliographic-documentary means, with a descriptive-exploratory objective